1997
DOI: 10.1002/(sici)1096-9861(19971208)389:1<161::aid-cne12>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Starburst cholinergic amacrine cells in the tree shrew retina

Abstract: In all mammalian retinae studied to date, starburst cholinergic amacrine cells are a consistently occurring cell type. Here, we show that the cone-dominated retina of the tree shrew also has starburst cells with the characteristic radially symmetric branching pattern known from other species. Dendritic field sizes increase from 150 microm in the central retina to 300 microm in the retinal periphery. The characteristic morphology is established early during postnatal development. Labelling the starburst choline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Through the optimization of standard immunohistochemistry protocols, cholinergic amacrine cells which play key roles "in originating retinal directional selectivity and optokinetic eye movement" (Yoshida et al, 2001) could be detected 2 weeks earlier than had been reported previously (Sandmann et al, 1997). This helped to demonstrate that, in mammals, two mirror-imaged subpopulations of cholinergic amacrine cells are derived from a single population of precursor cells (Fig.…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…Through the optimization of standard immunohistochemistry protocols, cholinergic amacrine cells which play key roles "in originating retinal directional selectivity and optokinetic eye movement" (Yoshida et al, 2001) could be detected 2 weeks earlier than had been reported previously (Sandmann et al, 1997). This helped to demonstrate that, in mammals, two mirror-imaged subpopulations of cholinergic amacrine cells are derived from a single population of precursor cells (Fig.…”
Section: "Starburst" Amacrine Cellsmentioning
confidence: 85%
“…Different from photoreceptor cells in mice and men, the nuclei of these cones are not stacked upon one another, but clearly arranged in only one row. Consequently, both the development of cones and rods (Knabe, 1995;Knabe and Kuhn, 1996a, b, 1997, 1998a and the establishment of the associated neural networks can be studied under particularly favorable conditions (Müller and Peichl, 1991a, b;Engelmann and Peichl, 1996;Sandmann et al, 1997;Knabe et al, 2007). On the other hand, the tree shrew retina is consulted in clinical contexts due to its extensive structural similarity to the primate retina, e.g., for documentation of retinal thinnings following induced high myopia via in vivo optical coherence tomography (Abbott et al, 2009(Abbott et al, , 2011.…”
Section: "Lens Mitochondria" In the Cone Inner Segmentsmentioning
confidence: 99%
“…Cholinergic amacrine cells are wide-field neurons that stratify in one of two layers within the inner plexiform layer (IPL). Because of their dendritic extent, these neurons typically exhibit dendritic coverage factors far in excess of the other neurons mentioned above, ranging from 10 to 70 depending on the species (Tauchi & Masland, 1984;Vaney, 1984;Schmidt et al, 1985;Voigt, 1986;Rodieck & Marshak, 1992;Sandmann et al, 1997). How these cells regulate their dendritic extent, as well as their positioning, is unclear, but their density and dendritic field size should permit ample opportunity for interactions with neighboring cells during development.…”
Section: Introductionmentioning
confidence: 99%
“…It is found only in two types of amacrine cells, known as "starburst cells," across species: one is found in the inner nuclear layer (INL) and the other forms a displaced population in the ganglion cell layer (GCL). The dendrites from each population ramify within the inner plexiform layer (IPL), with the dendritic plexus of the amacrine cells from the INL confined to sublamina a, whereas those of the displaced amacrine cells are confined to sublamina b (cat: Schmidt et al 1985;Pourcho and Osman 1986;mouse: Jeon et al 1998;Haverkamp and Wässle 2000;primate: Mariani and Hersh 1988;Rodieck and Marshak 1992;rabbit: Famiglietti 1983;Brandon 1987;Famiglietti and Tumosa 1987;rat: Voigt 1986;Mitrofanis and Stone 1988;Kim et al 2000; tree shrew: Conley et al 1986;Sandmann et al 1997). These amacrine cells are known to be involved in movement detection (Ariel and Daw 1982;Masland and Tauchi 1986;Taylor et al 2000;Yoshida et al 2001;Euler et al 2002) and optokinetic eye movements (Yoshida et al 2001).…”
Section: Introductionmentioning
confidence: 99%